CRIMINAL COURTS IN UZBEKISTAN: FORMATION, DEVELOPMENT, AND INSTITUTIONAL REFORMS - Anvar Fayzullayev (Modern American Journals, 2025)
This article examines the formation and development of criminal courts in Uzbekistan as an independent institution. The study analyzes judicial reforms, organizational changes, court efficiency, and mechanisms for the protection of human rights.
Keywords: Criminal courts, judicial reforms, independent judiciary, human rights.